2010
DOI: 10.1016/s1470-2045(10)70207-2
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel-lymph-node resection compared with conventional axillary-lymph-node dissection in clinically node-negative patients with breast cancer: overall survival findings from the NSABP B-32 randomised phase 3 trial

Abstract: SummaryBackground-Sentinel node surgery was designed to minimize side effects of lymph node surgery but still offer outcomes equivalent to axillary dissection. The aims of NSABP Protocol B-32 were to determine whether sentinel node resection in breast cancer patients achieves the same survival and regional control as axillary dissection but with fewer side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
908
2
35

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,613 publications
(975 citation statements)
references
References 35 publications
30
908
2
35
Order By: Relevance
“…106 In these patients, excision of all regional lymph nodes from the axilla compared with excision of sentinel lymph node alone did not result in additional benefit. 107,108 Therefore, it was concluded that removal of the sentinel lymph node might be sufficient and more extensive removal of axillary nodes was not recommended in patients without sentinel lymph node metastasis.…”
Section: The Role Of Vegfs In Lymphangiogenesismentioning
confidence: 99%
“…106 In these patients, excision of all regional lymph nodes from the axilla compared with excision of sentinel lymph node alone did not result in additional benefit. 107,108 Therefore, it was concluded that removal of the sentinel lymph node might be sufficient and more extensive removal of axillary nodes was not recommended in patients without sentinel lymph node metastasis.…”
Section: The Role Of Vegfs In Lymphangiogenesismentioning
confidence: 99%
“…It was concluded that when SLN is histologically free from disease, Sentinel Lymph Node Dissection (SLND) alone with no further ALND is safe, appropriate and effective therapy for patients with clinically node negative breast cancer. The morbidity results also showed the obvious superiority in the second group [5,6].…”
Section: The Existing Evidence For Slnb In Addressal Of Axillamentioning
confidence: 82%
“…The National Cancer Institute (NCI) conference however concluded that SLNB can be performed before or after NACT in patients with clinically node negative cancer. SLNB is associated with less than 1 % isolated axillary recurrence in node negative disease and provides an excellent regional nodal control [5,6]. The author has published a validation study indicating the reliability of SLNB using dye alone method in patients after neo-adjuvant chemotherapy [4].…”
Section: The Existing Evidence For Slnb In Addressal Of Axillamentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure, however, also exposes 78% of early stage breast cancer patients to overtreatment with a 16% risk of lymphedema in five years [8]. With the appearance of the lymphatic mapping technique, three seminal studies, MILAN, NSABP-B32, and ALMANAC trials established sentinel lymph node biopsy (SLNB), a much less invasive procedure, as the new standard for staging of the axilla [9][10][11][12]. In all three studies, SLNB was compared to AD for axillary staging in clinically node-negative patients reporting a 5-10% false negative rate (FNR) and 90% identification rate (IR) with equivalent disease-free survival (DFS) and overall survival (OS).…”
Section: Reviewmentioning
confidence: 99%